Assessing the trend of weather parameters and their effect on rice and jute yields in southern part of West Bengal - S. CHAUDHURY; K. CHATTERJEE; S. BANERJEE (Journal of Agrometeorology)
Considering the global concern on climate change, understanding the spatiotemporal variability of meteorological variables and their impact on crop yield is crucial for an agricultural nation like India.  In this work, we have analyzed the temperature and rainfall data for seven decades (1951-2020) over the southern part of West Bengal represented by four grid points using Mann-Kendall test and Sen's slope estimator. The results showed no significant trend in average annual maximum temperature, whereas, the average annual minimum temperature exhibited increase in trend at 95 % significance level among all the grids. However, the total yearly rainfall showed no trend, apart for the grid region centered in Bardhaman district showing an increasing trend. The correlation between 23 years (1997-2019) of yield data and climatic variables for different phenophases ranges from  -0.47 to +0.72 for Kharif rice and -0.47 to +0.60 for jute. Climatic variables averaged over crop phenophases exhibit finer characteristics compared to annual averages and bear significant influence on yield variability as shown by multiple linear regression. Regression analysis indicate that  temperatures play a more influential factor in determining Kharif rice yields than rainfall and yield equations pertaining to rice exhibits better sensitivity to varying climate than those representing jute yields.